Implementation of Fault Tree Analysis on Delays in the Production Process of Palm Kernel Shell Conveyor Project at PT Berkah Anugerah Inti Semesta: Terapan Fault Tree Analysis Pada Keterlambatan Proses Produksi Proyek Conveyor Cangkang Sawit pada PT Berkah Anugerah Inti Semesta - Alvin Rizky Syahputra; Yekti Condro Winursito (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
PT Berkah Anugerah Inti Semesta is a company engaged in the fabrication sector. One of its products is a palm shell conveyor. One of the challenges of the production process faced is production delays that can have an impact on operational efficiency and customer satisfaction. This study aims to analyze the causes of delays in the conveyor production process using the fault tree analysis method. The analysis was carried out during the production process in the workshop area. The results of the analysis showed a delay in the processing time, from three weeks to one month. This was due to problems in the fit-up, full weld, visual cleaning, and machining processes. This study produces recommendations based on the results of the analysis which are expected to reduce the level of delays in the production process.